Hot cocoa hearts - Nelson, Suzanne, 1976- (Wish (Scholastic Inc.), 2016)
Emery Mason is not a fan of Christmas, but she must work at her parents' shop in the mall during the holiday. There she meets Alex who works at the hot cocoa shop next door. Although Em is crushing on Sawyer, Alex helps her enjoy the holidays. Soon a blizzard and a Secret Santa surprise make Em question just which boy she wants to kiss under the mistletoe.